Memorial dedicated to George Warden - Ghosh, Ayan (2023)
Among works commissioned by English sculptor John Bacon Jr. is this memorial dedicated to artillery captain George Warden, who served in the Bombay army and died on 16th October 1807 at the village of Choor-Verah at the age of 32. The mourning scene depicts Affection (left), grieving over the body of the captain placed on a bed, and Faith (right), seen holding a book and making a gesture to the departing soul of George Warden (top).